Investigación para la gestión empresarial y la innovación - Bustamante Penagos, Laura Estefany (Corporación Universitaria Americana, 2018)
The text presented here, entitled "Research for business management and innovation", is a product of the rapprochement between academia and the business sector to generate knowledge from the practical interaction between these two important actors of society. In its contents, the reader will find the most relevant results of the development of actions within organizations, which allow the resolution of problems and the management of competitiveness and innovation. These last two concepts have been part of the debate on the future of Colombia, so that government actions are established to visualize the strategies that allow this to become a reality for the country.